Optimizing SPPG Services Through the Implementation of Digital Technology to Support the Free Nutritional Meal Program (MBG) - Anzas Ibezato Zalukhu; Irwan Syahputra; Maida Indrayani; Ayu Ofta Sari; Suhardiansyah; Dewi Sartika; Bambang Sugito (Jurnal Pengabdian Masyarakat Variasi, 2026)
The Free Nutritional Meal Program (MBG) is a national strategic program aimed at improving the nutritional quality of the community, particularly students. One of the challenges in its implementation is the delay in food distribution, which can affect the quality of service and the effectiveness of the program. This Community Service Activity aims to improve the understanding and capabilities of managers and officers of the Nutrition Fulfillment Service Unit (SPPG) in utilizing digital technology through the implementation of a food distribution route optimization application. The activity was carried out at the SPPG in Baru Pasar VIII Village, Tanjung Beringin, Hinai District, Langkat Regency, using methods such as socialization, training, demonstrations, and simulations of application use. The materials provided covered the concept of service digitization, distribution route optimization, and practical use of digital map-based applications. The results of the activity showed an increase in participants' understanding of the importance of digital technology in supporting MBG operations, an increase in their ability to use the route optimization application, and an increased awareness of the importance of efficiency and timeliness in food distribution. Participants also responded positively to the implementation of a system that can help determine more effective and efficient delivery routes. The implementation of digital technology through the route optimization application has been proven to support the improvement of SPPG service quality in implementing the Free Nutritional Meal Program in a more timely, efficient, and sustainable manner.